Work culture and developing agri-entrepreneurial skills among farmers - Mohamed, Zainal Abidin; Rezai, Golnaz; Apriyanti, Ira; Abdullah, Amin Mahir; Tamam, Ezhar (Science Publications, 2011)
Problem statement: The government of Malaysia has established several agencies within the Ministry of Agriculture and agri-based Industry such as the Farmers’ Organization Authority to provide technical and motivational training to individual members involved in farming practices to become agri-entrepreneurs. Approach: The objectives of the study are to identify and determine the entrepreneurial work culture as perceived by Farmers’ Organization Authority members. Members of Farmers’ Organization Authority were interviewed via a structured questionnaire. The factor analysis determines 6 latent factors that were realized by the Farmers’ Organization Authority members as being important for promoting an entrepreneurial work culture and therefore should be enhanced and re-inculcated among the Farmers’ Organization Authority farming community. Results: These factors translate into the community having to become more innovative, responsible and accountable, profit oriented, visionary, better at performing their study practices in a more systematic way and finally to become more self confident. Conclusion/Recommendation: Efforts should be intensified to encourage Farmers’ Organization Authority members with training to focus not on modern technologies only, but on enhancing the entrepreneurial work culture and fundamental changes in attitude towards treating farming as a business. Formal entrepreneurship training should be instituted to all Farmers’ Organization Authority members who are interested in taking a loan in enhancing their farming activities. This conditionality can be implemented to ensure that the loan is being spent accordingly and the development of agri-entrepreneurship skills can be enhanced.